SEASONAL DISTRIBUTION OF SOME OCEANOGRAPHIC PARAMETERS OFF SOUTHWEST COAST OF INDIA RELEVANT TO PELAGIC FISHERIES - Murty, A V S; Vishnudatta, M N (Indian Journal of Fisheries, 2011)
Hydrographic condftions of the upper mixed layer play a dominant role in the behaviour of the pelagic fishes and hence their fisheries. Murty (1965) studied the behaviour of the mixed layer and thermocline ofl the southwest coast of India. Sharma (1966) correlated the seasonal changes of the level of discontinuity layer with vertical motions (upwelling and sinking). Banse (1968) reviewed the hydrography of the region with a view to detecting the influence of upwelling on the demersal fisheries. We make an attempt here to correlate the pelagic fisheries for oil sardine and mackerel with temperature, salinity and oxygen conditions of the waters associated with the thermocline off the southwest coast of India.